Dementia and aging in Vietnam - Dung, Nguyen Thi Phuong (Magyar Gerontológia, 2024)
The aging rate of the Vietnamese population is one of the most elevated worldwide. Dementia is identified as one of the major disturbances to healthy aging and a leading cause of death in Vietnam. In spite of the importance of dementia research for policy making and healthcare development, there is a scarcity in study on epidemiological profile of dementia in Vietnam.